Hubungan Kekuatan Genggaman Tangan dengan Fungsi Ekstremitas Atas pada Lansia di Panti Jompo Denpasar - Sabila Harianti; Sayu Aryantari Putri Thanaya; Indah Pramita; Anak Ayu Nyoman Trisna Narta Dewi (KOLONI, 2026)
Older adults experience aging processes that may cause decreased muscle mass and muscle strength, including hand muscle strength. Reduced handgrip strength can affect the ability of older adults to perform daily activities involving the upper extremities, such as gripping, lifting, carrying, and manipulating objects. This study aimed to determine the relationship between handgrip strength and upper extremity function in older adults at nursing homes in Denpasar. This study used an analytical cross-sectional design. A total of 25 older adults were recruited using total sampling. Handgrip strength was measured using a handgrip dynamometer, while upper extremity function was assessed using the Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) questionnaire. Data were analyzed using Spearman correlation. The results showed that the mean age was 70.16 +/- 3.934 years, mean handgrip strength was 15.172 +/- 6.438 kg, and mean QuickDASH score was 18.04 +/- 15.307. Spearman correlation analysis showed a significant relationship between handgrip strength and upper extremity function (r = -0.744; p = 0.000). Higher handgrip strength was associated with lower QuickDASH scores, indicating better upper extremity function. In conclusion, handgrip strength is significantly associated with upper extremity function in older adults at nursing homes in Denpasar.